Car ownership: state of the art of modelling and empirical findings - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
Car ownership level is probably one policy of the variables that has become a topic for continuous debates for many years. The factors affecting car ownership level are often very complicated that people might not be able to make an estimate of the car ownership level, not at the personal level nor at the household level. The literature has been demonstrated many approached used in the model but there is not yet an agreement on the general approach model. The saturation factor put forward by some research has provided more complications. On the one hand, the idea of saturation level can be regarded as a brilliant one since it represents the ultimate level of socio-economic behaviour as well as a system capacity. On the other hand, the determination of saturation level, which is normally decided exogenously, is regarded by many as far from satisfying. Some argued that the saturation level is virtually impossible to predict since the level itself is also a dynamic. In the research it is proposed to adopt Quarmby and Bates method with modifications, mainly to avoid the use of saturation level. Indonesian national data on car ownership shows that income is the most predominant factor affecting car ownesrhip. The existence of enormuous demand for car ownership has made the population density exempted from the model for Indonesian car ownership.